Bacterial involvement in otitis media with effusion - Daniel, M.; Imtiaz-Umer, S.; Fergie, N.; Birchall, J.P.; Bayston, Roger (Elsevier, 2012)
Objective Otitis media with effusion (OME), a common chronic childhood condition affecting hearing, is thought to be a result of bacterial infection, with biofilms recently implicated. Although bacterial DNA can be detected by polymerase chain reaction in 80% of patients, typically fewer than half of effusions are positive using standard culture techniques. We adopted an alternative approach to demonstrating bacteria in OME, using a bacterial viability stain and confocal laser scanning microscopy (CLSM): staining allows detection of live bacteria without requiring growth on culture, while CLSM allows demonstration of the three-dimensional structure typical of biofilms.